Aging, Elderly and Quality of Life: Success or Difficulty? - Teresita de Jesús Martínez Pérez; Caridad María González Aragón; Gisela Castellón León; Belkis González Aguiar (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
In this century, life is something that many have called a "unique moment" because for the first time in history various generations coexist. This demographic dynamics in the world and in Cuba in particular, is an achievement and at the same time a challenge. Identifying that this phenomena involves the health area and other sectors of the society and in addition it requires inclusive and creative resources in public policies so this is life extension with quality, is indispensable for sustainability. The new conceptions in gerontologic field lead us to a need of multidiscipline and multisectorial integration, not only to face the population aging from the social point of view but also, from the individual perspective, to learn aging with quality. The objective of this work is present some of the challenges it implies to facing the population aging so that older adults may age with a higher quality if life.